(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2024)
The study in this review aims to know and study the parasite Entamoebahistolytica that causes Amoebiasis worldwide. During its life cycle, E. histolytica passes through several phases, trophozoite stage, precyst stage, the cyst stage, the Metacyst stage, and Metacystictrophozoite stage. In this study, the spread of the parasite globally and in the Arab world and methods of treating the disease were also discussed. The Genomic structureof E. histolytica, like other organisms, is characterized by diversity and heterogeneity in its genetic content, which is one of the most important reasons for its survival and its ability to infect. Interestingly, the genome of the E. histolytica contains a large amount of genes presumed to be of bacterial origin. The study of the genetic diversity of E. histolytica gives paths to the developmental change that resulted in the emergence of evolutionary features or traits. Understanding amoebic virulence is important. Several studies have shown that genetic factors influence the virulence of parasitic infections. Studying the virulence of E. histolytica by Serine-rich protein (REHP) gene is among the important issues used in molecular epidemiological studies.